2022
DOI: 10.1007/s40263-022-00899-0
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of Nusinersen Levels Following Treatment Interruption in People With Spinal Muscular Atrophy: Simulations Based on a Population Pharmacokinetic Model

Abstract: Background Nusinersen is approved for the treatment of spinal muscular atrophy. The most common approved dosing regimen is four intrathecal loading doses of nusinersen 12 mg; the first three are administered at 14-day intervals followed by a fourth dose 30 days later, and then 12-mg maintenance doses are administered every 4 months thereafter. Interruption of nusinersen treatment in the maintenance dosing phase might occur for a number of clinical reasons. Objective The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
(52 reference statements)
0
5
0
Order By: Relevance
“…The subsequent dose may then be maintained according to the previously defined schedule. Detailed advice based on clinical trial analysis and pharmacokinetic studies is available 152 and is reassuring that only prolonged omission of eight months or more should require additional dosing.…”
Section: Discussionmentioning
confidence: 99%
“…The subsequent dose may then be maintained according to the previously defined schedule. Detailed advice based on clinical trial analysis and pharmacokinetic studies is available 152 and is reassuring that only prolonged omission of eight months or more should require additional dosing.…”
Section: Discussionmentioning
confidence: 99%
“…In the event that patients do miss a dose of nusinersen, population pharmacokinetic modeling has shown that nusinersen levels can be rapidly restored following a dose delay of up to 4 months in the maintenance phase of treatment. This is done by administering the delayed dose as soon as possible; then, the subsequent dose is administered according to the original scheduled date, as long as these two doses are administered at least 14 days apart, followed by a dose every 4 months thereafter [ 30 , 32 ]. For a second or third loading dose delayed by 30–90 days, it is recommended to resume the loading dose as soon as feasible and shift all remaining doses by the same number of days delayed [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“… Local sites for the collection of blood samples, or mobile collection at patients’ homes [ 34 , 44 , 46 ]. A plan for how to maintain the treatment administration schedule whenever possible while preserving patient safety [ 29 , 30 , 47 ]. Remote physical therapy sessions [ 43 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…A plan for how to maintain the treatment administration schedule whenever possible while preserving patient safety [ 29 , 30 , 47 ].…”
Section: Discussionmentioning
confidence: 99%